Buzzy e DistrACTION na redução da dor durante a vacinação infantil: ensaio clínico randomizado - Fontes, Viviane Santos (2019)
Background: childhood is marked by procedures that involve the use of the needle. Among them is vaccination, the most common source of iatrogenic pain among children. The discomfort associated with needle procedures can trigger phobia, a significant barrier to the health of children and adults. Objective: To compare the effect of Buzzy® and Distraction® devices on pain relief in infants during injectable vaccination. Method: Randomized controlled clinical trial and double blind developed at a Basic Health Unit (UBS) in Aracaju, Sergipe, Northeast of Brazil. The simple random sample consisted of children aged 2 to 4 years, who attended the UBS for vaccination. They were randomized into three groups: two intervention groups: Buzzy® and Distaction®; and a control group. Anxiety was measured through the Infant Fear Scale, while in Pain the Wong-Baker Face Scale was used. The study was approved by the Ethics and Research Committee of the Federal University of Sergipe (opinion number: 2 801 596), registered in the Universal Trial Number (number: U1111-1224-4940) and in the Brazilian Registry of Clinical Trials (primary identifier: RBR- 5npk9s). Results: pain and anxiety among children had reduced rates in the experimental groups, in relation to the control group, demonstrating the effectiveness of the devices. However, Distraction® was more effective than Buzzy® in relieving pain [5,6 (3,2) vs. 6,1 (3,4), p= 0.078] and anxiety [1,9 (1,2) vs. 2,3 (1,3), p= 0.157]. Conclusion: Buzzy® thermomechanical stimulation and distraction with Distraction® are effective tools to reduce pain and anxiety in children during vaccination and can be implemented in nursing practice.